Autoantibodies against thrombospondin type 1 domain–containing 7A induce membranous nephropathy - Nicola M. Tomas; Elion Hoxha; Anna T. Reinicke; Lars Fester; Udo Helmchen; Jens Gerth; Friederike Bachmann; Klemens Budde; Friedrich Koch‐Nolte; Gunther Zahner; Gabriele M. Rune; Gérard Lambeau; et al. (2016)
Membranous nephropathy (MN) is the most common cause of nephrotic syndrome in adults, and one-third of patients develop end-stage renal disease (ESRD). Circulating autoantibodies against the podocyte surface antigens phospholipase A2 receptor 1 (PLA2R1) and the recently identified thrombospondin type 1 domain–containing 7A (THSD7A) are assumed to cause the disease in the majority of patients. The pathogenicity of these antibodies, however, has not been directly proven. Here, we have reported the analysis and characterization of a male patient with THSD7A-associated MN who progressed to ESRD and subsequently underwent renal transplantation. MN rapidly recurred after transplantation. Enhanced staining for THSD7A was observed in the kidney allograft, and detectable anti-THSD7A antibodies were present in the serum before and after transplantation, suggesting that these antibodies induced a recurrence of MN in the renal transplant. In contrast to PLA2R1, THSD7A was expressed on both human and murine podocytes, enabling the evaluation of whether anti-THSD7A antibodies cause MN in mice. We demonstrated that human anti-THSD7A antibodies specifically bind to murine THSD7A on podocyte foot processes, induce proteinuria, and initiate a histopathological pattern that is typical of MN. Furthermore, anti-THSD7A antibodies induced marked cytoskeletal rearrangement in primary murine glomerular epithelial cells as well as in human embryonic kidney 293 cells. Our findings support a causative role of anti-THSD7A antibodies in the development of MN.